Screw complication of ACL reconstruction: report of two cases - Che Ahmad, Aminudin; Ismail, Raffael; Zakaria@Mohamad, Zamzuri; Zulkifly, Ahmad Hafiz (2010)
Background: We analyzed the comlication of ACL reconstruction of the knee which were done at Hospital Tengku Ampuan AFzan, Kuantan, Pahang from 2004 to 2008. Hundrend and sixty-three cases were operated. Complication rate is about 11% (18 patients)including revision surgery rate of 3.7% (6 patients). We are illustrating two case with uncommon complication of srew that encountered in ACL surgical reconstructed patients. Case 1: 28 year old man had undergo ACL reconstruction at 2004 using bone patella tendon bone (BPTB)graft and fixed with titanium screw. However, the femoral screw was dislodging posteriorly and remains there for there years until he was consented for open removal of the screw. Post-operatively uneventful. Case 2: 22 years old man presented in August 2009 with the tibial screw protruding through the skin since a week prior to the consultation. The ACL reconstruction was done 2 years before (2007). Emergency removal of screw and debridement revealed well fixed screw without loosening an d no evidence of infection. Histopathological review and cultures and sensitivity did not found any evidence of infection. The knee remains stable without any laxity. Conclusion: Using of screws for fixation of the graft in ACL reconstruction carefully and appropriately is mandatory to avoid the complication of both at the femoral and tibial components.